Words are not for hurting - Verdick, Elizabeth; Heinlen, Marieka (Minneapolis, Minn. : Free Spirit Pub., 2004)
Encourages toddlers and preschoolers to express themselves using helpful, not hurtful, words. Includes a note for parents and caregivers.
Includes bibliographical references (p. 32).
Keywords: Conversation -- Juvenile literature; Etiquette for children and teenagers; Conversation; Etiquette; Interpersonal conflict